The Meaning of Green Light in The Great Gatsby Based on Consumerism Perspective: Umberto Eco’s Semiotic Study - Mulatsih, Maria Vincentia Eka (Universitas Sanata Dharma, 2015)
One of recent problems in our country is the habit of being consumerist – buying things which are not needed to update the trend. Some people think that it is not a big problem, but some do not. Avoiding its negative effect is the answer to this problem. This can be done through learning past experiences in the literary works, in this case Fitzgerald’s novel. The Great Gatsby depicts not only love but also consumerism. Through analyzing the sign of green light using Umberto Eco’s semiotic theory, we can see the bad effect of consumerism in the past and anticipate it for our future by applying its oppositional structure. The sign of green light is not merely an orgiastic feature. It is a tool for Fitzgerald to ‘fight’ consumerism effect.